2018
DOI: 10.1021/acs.jpcc.8b11500
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Band Structure Evolution of Halide Perovskites: A First-Principles Atomic and Electronic Structure Study

Abstract: Density functional theory (DFT) based calculations have been conducted to draw a broad picture of pressure induced band structure evolution in various phases of organic and inorganic halide perovskite materials. Under a wide range of pressure applied, distinct band structure behaviors including magnitude change of band gap, direct-indirect/indirect-direct band gap transitions and CBM/VBM shifts, have been observed between organic and inorganic perovskites among different phases. Through atomic and electronic s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 36 publications
2
56
0
Order By: Relevance
“…As suggested, the bandgap of perovskite materials is highly variable based on the overlap of electronic wave functions between metal B and halide X ions . Figure a shows the first‐principles DFT calculated bandgap versus pressure.…”
Section: Resultsmentioning
confidence: 99%
“…As suggested, the bandgap of perovskite materials is highly variable based on the overlap of electronic wave functions between metal B and halide X ions . Figure a shows the first‐principles DFT calculated bandgap versus pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Computational studies of the tunable properties such as electronic structures under external pressure for MAPbX 3 (X = I, Br, Cl) and all‐inorganic halide perovskites CsMX 3 were reported. [ 91–94 ] Using first‐principles calculations, Liu et al. [ 95 ] found that CsPbI 3 under appropriate strain engineering exhibited ferroelectric and topological orders simultaneously, namely a ferroelectric topological insulator.…”
Section: Fundamental Structure Parameters and Properties Of Bulk Peromentioning
confidence: 99%
“…8 There have been extensive theoretical works studying the structure and electronic, optical, and defect properties of MAPbI 3 , and these have greatly deepened the understanding of MAPbI 3 and accelerated research into its application to devices. [14][15][16][17][18][19] Although there have been some of theoretical works studying FAPbI 3 , 20-24 a systematic and comprehensive study is still absent. Pan et al investigate the geometric and electronic structures of hybrid organic-inorganic perovskites FAPbX 3 (X ¼ Cl, Br, I).…”
Section: Introductionmentioning
confidence: 99%